ANALYSIS OF ANTIOXIDANT AND ANTIBACTERIAL ACTIVITY ETANOL EXTRACT OF BUTTERFLY PEA FLOWER (Clitoria ternatea) IN YOGYAKARTA - Kusuma, Nyoman Rudi; Sulistyani, Nanik; Sugihartini, Nining (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Butterfly Pea Flower is one of the plants that has antioxidant activity. However, based on previous studies, the antioxidant content is highly dependent on the location and place of the BPF itself. Therefore, this study aims to measure the concentration of total flavonoids, phenolics, antioxidant and antibacterial activity in BPF so that this research can be further developed into certain products. Extraction using maceration method with 96% ethanol solvent (1:10). DPPH method for measuring antioxidant activity and the disc paper diffusion method for testing antibacterial activity. BPF contain flavonoids and total phenolics of 19.44 ± 0.060 mg Quercetin Equivalent (QE)/g and 36.37 ± 0.47 mg Gallic Acid Equivalent (GAE)/g, respectively. BPF also contains antioxidants with an IC50 index of 49.47 µg/mL and BPF extract has no antibacterial activity using the paper disc diffusion method. This antioxidant-rich BPF extract has a lot of promise for development into a cosmetic preparation with more research. Keywords: Butterfly Pea Flower, Antioxidant, Antibacterial, Flavonoid, Phenolic.